Analisis Efektivitas Pemberian Insentif Pajak Dalam Rangka Penerimaan PBB-P2 Pada Masa Pandemi Covid-19 Di UPT Pajak Daerah Caringin, Kabupaten Bogor Tahun 2021 - Adinda Safira Isfahani; Mainita Hidayati (Jurnal Ilmu Administrasi Publik, 2023)
The Covid-19 pandemic has caused a decline in the people’s economy. Hence, the Regional Government of Bogor Regency tried to minimize the impact by implementing a policy of providing tax incentives including PBB-P2 (Rural and Urban Land and Building Tax). This research was conducted to determine the effectiveness of providing tax incentives, the obstacles encountered and the efforts made in the context of PBB-P2 revenue during the Covid-19 pandemic. This study was conducted at the Caringin Regional Tax Technical Implementation Unit (UPT) of Bogor Regency. The descriptive qualitative method was used in this study by interviews and documentation studies. According to Duncan, effectiveness can be seen through goal attainment, integrity and adaptation. The findings of this study indicated that the policy of providing tax incentives at the Caringin Regional Tax Technical Implementation Unit (UPT) was still ineffective in PBB-P2 revenue, because not all indicators of effectiveness according to Duncan were fulfilled. The unfulfilled indicators were goal attainment because the realization of PBB-P2 revenue did not meet the target and integration because there were still many taxpayers with no awareness to pay PBB-P2. The fulfilled indicator was adaptation because the Caringin Regional Tax Technical Implementation Unit (UPTPD) employees were able to adapt to existing procedures during the Covid-19 pandemic, and the facilities and infrastructure available were sufficient.